Isolation and Molecular Characterisation of Listeria Monocytogenes and Listeria Innocua from Poultry Meat - Bilung, Lesley Maurice (2002)
Thirty isolates of Listeria monocytogenes (12) and Listeria innocua (18) were isolated from poultry meat. All isolates were confirmed by Microbact (Medvet, Australia) identification kits. All the isolates were subjected to chromosomal and plasmid DNA screening and antibiotic resistance test. Based on the antibiotic resistance profiles, Listeria monocytogenes and Listeria innocua were differentiated into 10 and 9 profiles respectively. The antibiotyping procedure discriminated the Listeria monocytogenes and Listeria innocua into 10 and 3 different groups respectively. Most of the isolates were resistant to nalidixic acid (100%), c1indamycin (97%), spectinomycin (97%), cefuroxime (93%), cefriaxone (80%), cephalothin (73%), cefotaxime (67%), novobiocin (37%), chloramphenicol (27%), kanamycin (20%), rifampicin (20%), tobramycin (17%), norfloxacin (13%), netilmicin(10%) and imipenem (3%). The results of the plasmid profiles and antibiotyping show that there is no correlation between them. RAPD-PCR has been used to generate polymorphic genomic fingerprints to discriminate the Listeria isolates. Primer GEN15009 was chosen whereby it produced reproducible and typeable results in all isolates examined with the bands ranging from 0.25 to 3.0 kilobase pairs. From the dendrogram generated L. monocytogenes were separated from L. innocua and the strains in each species were differentiated as well. The data indicate that RAPD-PCR based approaches is a valid means of discriminating strain differences among isolates of L. monocytogenes and L. innocua and as an adjunct to differentiate among Listeria spp.